Millets: The future crops for the tropics - Status, challenges and future prospects - Sinthia Afsana Kheya; Shishir Kanti Talukder; Prantika Datta; Sabina Yeasmin; Md. Harun Rashid; Ahmed Khairul Hasan; Md. Parvez Anwar; A.K.M. Aminul Islam; A.K.M. Mominul Islam (Heliyon, 2023)
Millets are small-grained nutritious minor cereal crops that are resistant to different abiotic stresses resulting from climate change. Despite their many benefits, millets have received limited attention in agricultural research, policies, and markets. Considering the importance of millets, recently the government many tropical countries including India and Bangladesh give more emphasis to millets cultivation and improvement. Moreover, Food and Agricultural Organization of the United Nations (FAO) declared 2023 to be the “International Years of Millets”. In these connections, a details and updated review of the pros and cons of millets cultivation and its improvement in this region warrant due attention. The review therefore, examines the potential and main barriers to the adoption and promotion of millet cultivation in this region. These include limited research and development efforts, inadequate infrastructure and inputs, weak market linkages and demand, and insufficient awareness and knowledge about millets' nutritional and environmental benefits. This review also highlighted the prospects and strategies for scaling up millet cultivation in this region especially in Bangladesh. These include increasing public and private investment in research and extension services, strengthening farmers' organizations and market linkages, promoting millet-based value chains and products, and integrating millets into nation’s food policy. The review concludes that millets might support equitable and sustainable agricultural growth, which would contribute to global food and nutritional security and could help attain the sustainable development goals (SDGs). However, achieving this potential will require concerted efforts from multiple stakeholders, including farmers, researchers and policymakers. The review emphasizes the need for a multi-disciplinary and multi-stakeholder approach that prioritizes innovation, inclusiveness, and sustainability. Lastly, the review highlights more investigation into the socioeconomic, environmental, and nutritional effects of millet production in this region with special emphasis on Bangladesh in order to support evidence-based policies and practices.